MISI GEREJA DALAM KONTEKS ASIA - Merry Teresa Sri Rejeki (Litbang STFT Widya Sasana Malang, 2003)
Mission is the very nature of Church’s existence. One of the current theological movements is what we call “contextualisation”. In line with such theological movement, the church in Asia is called to redefine his mission. A year ago the professors of the School of Philosophy and Theology, Widya Sasana, discussed systematically the issue of contextualisation: its meanings, bases, implications in connection with the Church’s mission in Asia. This brief article would draw some essential elements of doing contextualisation. The starting point of so doing is “Sentire cum Ecclesia”, a feeling that makes us conform our hope and concern to the Church. The second element dealt with is awareness of the context, which is an Asian reality with challenges to be coped. What should we do with mission is the concluding suggestion of this short elaboration.